2003
DOI: 10.1002/nau.10160
|View full text |Cite
|
Sign up to set email alerts
|

Frequency‐volume charts: A tool to evaluate bladder sensation

Abstract: In conclusion, bladder sensation during daily life can be evaluated by scoring the grade of perception of fullness on frequency-volume charts. During life voiding usually occurs without desire to void. The voided volumes at different sensations of fullness are comparable to the volumes at different sensations of filling during cystometry. Therefore, frequency-volume charts with evaluation of perception of fullness may provide an initial non-invasive tool to study bladder sensation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
122
1
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(132 citation statements)
references
References 22 publications
6
122
1
3
Order By: Relevance
“…Others have already suggested, that if urgency is a continuum, healthy people should also be able to perceive it [2,7]. In a study on sensation-related voiding charts, it was confirmed that healthy volunteers can perceive urgency or a CDV when trying to postpone voiding as long as possible [14]. We therefore propose that urgency should be considered more in terms of disturbed filling sensation.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Others have already suggested, that if urgency is a continuum, healthy people should also be able to perceive it [2,7]. In a study on sensation-related voiding charts, it was confirmed that healthy volunteers can perceive urgency or a CDV when trying to postpone voiding as long as possible [14]. We therefore propose that urgency should be considered more in terms of disturbed filling sensation.…”
Section: Discussionsupporting
confidence: 51%
“…The use of cystometry as the technique might put some limitations to the study, as inserting a transurethral catheter and filling the bladder artificially might already change the sensory pattern in patients, and it is unknown whether the cystometric filling sensations correlate with the filling sensations during normal daily life. In healthy volunteers the volume of the reported filling sensations correlate well between cystometry and voiding diaries [14], but no such data are yet available for patients.…”
Section: Discussionmentioning
confidence: 98%
“…However, the term OAB does not actually identify specific causes or disease entities (Yokoyama et al, 2008). Although the use of an urgency perception scale or urgency severity score has been suggested, these instruments are based on subjective reporting by the patient who must grade the degree of urgency and may be difficult for patients to understand the term of urgency (De Wachter and Wyndaele, 2003;Nixon et al, 2005). One way to overcome this problem is to introduce an objective test for the diagnosis of OAB.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with overactive bladder (OAB), the developement of an assessment scale and the evaluation of urgency, which is the most common complaint of OAB patients, is particularly important (10,11). Urodynamic study is the standard technique used for the evaluation of bladder sensation (7,12). Moreover, the voiding diaries, which are reliable and repeatable tests, can be used for the assessment of bladder sensation (13,14).…”
Section: Discussionmentioning
confidence: 99%